PENGARUH CARA DAN SIKLUS PETIK TERHADAP PRODUKSI DAN MUTU PUCUK TANAMAN THE (Camellia sinensis (L.) O. Kuntze) PRODUKTIF KLON RANCA BOLANG (RB) 3. - Ade Wachjar; , Supiyatno; Grace Prilensia Damayanty (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1998)
The objective of this experiment was to evaluate the effect of plucking method and cycle on shoot production and quality tea. The experiment was conducted at Gedeh Plantation, PTPN VIII, Cianjur, West Java from February to April 1997. The experiment was arranged in Randomized Block Design with 3 replications. The First factor was plucking method, consisted of hand plucking and scissor plucking. The second factor was cycle consisted of 3 levels: 3, 6, and 9 days. The result releaved that scissor plucking gave better production and better quality than hand plucking method, 9 days plucking cycle gave better production than 3 and 6 days plucking cycle, however 3 days plucking cycle gave better quality than 6 and 9 days plucking cycle. The highest production was obtained by combinations of 3 days plucking cycle with hand plucking